The role of antioxidant therapy in the treatment of male infertility: an overview - Lombardo, Francesco (Nature Publishing Group, 2011)
In recent years, many studies have focused on the effect of oxidative stress, reactive oxygen species (ROS) and antioxidants on the male eproductive system. Under physiological conditions, sperm produces small amounts of ROS, which are needed for fertilisation, acrosome reaction and capacitation. However, if an increased production of ROS is not associated with a similar increase in scavenging systems, peroxidative damage of the sperm plasma membrane and loss of DNA integrity typically occur, which leads to cell death and reduced fertility. Furthermore, since there is no linear correlation between sperm quality and pregnancy rates, an improvement in semen parameters should not be the sole outcome considered in studies of antioxidant therapies. A definitive conclusion regarding the benefit of these therapies is difficult to obtain, as most of the previous studies lacked control groups, considered different antioxidants in different combinations and doses, or did not evaluate pregnancy rates in previously infertile couples. Even if beneficial effects were reported in a few cases of male infertility, more multicentre, double-blind studies performed with the same criteria are necessary for an increased understanding of the effects of various antioxidants on fertility.